Improving the Usability and User Experience of a Ticketing and Knowledge Base Web Application: A Case Study of the ESDM 136 Contact Center - Ridwan Afandi; Santoso, Harry Budi (AI Society & STMIK Indonesia, 2025)
The Ministry of Energy and Mineral Resources (MEMR) established the ESDM 136 Contact Center to improve public service accessibility and quality, supported by ticketing and a knowledge-based web application for managing complaints. However, in 2023, the average response time for requests exceeded the SLA, indicating a need to evaluate the application systems to improve service efficiency. This study addresses the poor usability and user experience of the ticketing and knowledge-based web applications, as evidenced by below-average scores on the UEQ and PSSUQ. Utilizing a mixed-methods approach, including usability testing, cognitive walkthroughs, and open-ended questionnaires, this research identified twenty-one usability issues. Eighteen design improvements, guided by user-centered design principles, were implemented in a high-fidelity prototype. Post-improvement PSSUQ evaluations showed significant improvements, with post-intervention scores falling within the